Body composition, appetite‐related hormones, adipocytokines, and heart failure in adult patients with congenital heart disease: A preliminary study. (27th November 2017) - Shiina, Yumi; Murakami, Tomoaki; Matsumoto, Noriko; Okamura, Daisuke; Takahashi, Yuta; Nishihata, Yosuke; Komiyama, Nobuyuki; Niwa, Koichiro
Abstract: Objectives: To assess body composition and relationships among body composition, appetite‐related hormones, adipocytokines, and heart failure (HF) in adult patients with congenital heart disease (CHD). Patients: This prospective study enrolled 46 consecutive adult patients with CHD and 12 age‐matched healthy controls. The patients and control subjects were divided into four groups: 13 patients with Fontan circulation (group A), 16 patients with cyanosis (group B), 17 patients who previously underwent biventricular repair (group C), and 12 age‐matched healthy controls. Design: Body composition was measured using InBody730, and levels of appetite‐related hormones (ghrelin and leptin) and adipocytokines (leptin, interleukin‐6, and tumor necrosis factor‐α) were determined. Relationships of these measurements between severe HF, defined as New York Heart Association functional class III–IV and/or recent repeated unscheduled hospitalizations due to HF, were examined using univariate logistic analysis. Results: Mean patient age was 32.1 ± 7.4 years. The skeletal muscle mass was significantly decreased in groups A and B compared with that in controls. Interestingly, ghrelin levels in groups A and B were also significantly lower than those in controls. Univariate logistic analysis revealed that ghrelin level, percent body fat, and pulse oximetric oxygen saturation were significantly associated with severe HF. Conclusions: Patients with Fontan circulation and those with cyanosis might be at a risk of sarcopenia. Despite the decreased skeletal muscle mass and increased body fat, ghrelin levels in these patients were decreased. These changes might have a negative impact on HF in these patients.